ENGLISH INTRODUCTION PADA KOHAI KARATE DI DOJO RAUDHATUL JANNAH PERUMAHAN TIBAN RAYA BATAM - Mhd. Johan; Winda Evyanto; Gaguk Rudianto; Robby Satria; Zia Hisni Mubarak (PUAN INDONESIA, 2022)
Introduction in English is an important one to learn. By introduction we can adapt to everyone. This dedication aims to guide children in communicating with the interlocutor. In this service, the devotees find weaknesses in pronunciation and the use of grammar. So it needs to be developed for further. The ability to communicate using English is very important, so from now, we prepare the younger generation to face the future times. If children can communicate in English well then we feel happy and their parents also feel proud. In this occasion, the usage of the English in the students’ school is very seldom, so the devotees try to practice to use English in the every training. Beside that it gives motivation for the students and also to the parents of the students. Using English is not only for the introduction the students but also used in the presentation of the material.